PICKUP AND DELIVERY COSTS - PROPOSED OUTSOURCING MODEL - Kosovac, Amel; Muharemović, Ermin (Journal of Applied Engineering Science, 2021)
The active introduction and modern technologies application in the transport market greatly affect all transport branches and the ways of their business. Availability and mass usage of the internet and web services create a new ambiance of trade through online sales respectively e-commerce. The increase in internet sales has a direct effect on the business of courier companies. The increase in the number of shipments, especially in the B2C (Business-to-consumer) segment, is putting increasing pressure on costs for companies that do pickup and delivery. Companies are trying to adapt their business to the new challenges and conditions that prevail in the transport market through different cost management models. One way to manage costs is to outsourcing costs. This paper proposes a model cost calculation in outsourcing services for pickup and delivery shipments based on the number of stops.